Designing and Developing Supplemental Technology of PACI Model Materials through Blended Learning Methods - Effendi Limbong (Celt: A Journal of Culture, English Language Teaching & Literature, 2016)
The 21st century English teachers and lecturers are required to have competencies in translating Content Knowledge (CK), integrating various Pedagogical Knolwedge (PK) and implementing Technological Knowledge (TK) in order to produce effective and efficient teaching. This research reveals and describes researchers efforts and pre-service EFL teachers (PSEFLTs) roles in designing and developing the supplemental teaching and learning materials with PowerPoint, Audacity, Camtasia and Internet. To transform researcher roles and model to introduce and implement Technological, Pedagogical, and Content Knowledge (TPACK) framework, this research implemented blended learning: traditional face to face (F2F) and Facebook closed-group discussion (FBcgD) based on Project-Based Learning (PBL). This research employed the qualitative autobiography narrative of self-study from the researchers experiences to implement blended learning. Semi-structure interviews were conducted with four PSEFLTs of group A and five PSEFLTs of group B to seek the PSEFLTs experiences in designing and developing PACI model. The results suggested that blended learning is can effectively and efficiently integrate and implement the design and development of a PACI model. Most importantly both of researcher and two groups realized that in integration of TPACK during a Computer Literacy course, the subject matter may be shaped by the application of technology; teaching as well as learning might be changed by the use of technology and the way to represent and communicate specific lessons to students.